Mechanisms of Psychological Defense in Communication Between Students and Teachers - Mirkosimova H.M. (Scientific Trends, 2025)
This article explores the mechanisms of psychological defense that emerge in the communication between students and teachers in the context of higher education. Psychological defense mechanisms are unconscious strategies individuals use to protect themselves from emotional discomfort, anxiety, or perceived threats. Within the educational environment, these defenses can influence how students respond to feedback, authority, or academic stress, and how teachers react to classroom dynamics, student behavior, or professional expectations. The article analyzes the types of defense mechanisms most commonly observed in student-teacher communication, such as denial, projection, rationalization, and avoidance, and examines their psychological functions and pedagogical consequences. Special attention is given to cultural and institutional factors influencing these dynamics, especially within Uzbekistan’s higher education system. The paper also offers practical recommendations for recognizing, managing, and transforming defensive behaviors into constructive communication strategies that foster emotional safety, mutual respect, and effective interaction.
Keywords: Psychological defense, student-teacher communication, emotional regulation, higher education, projection, denial, rationalization, educational psychology, stress response, classroom dynamics.